2005
DOI: 10.1590/s0037-86822005000300004
|View full text |Cite
|
Sign up to set email alerts
|

Leishmaniose tegumentar americana causada por Leishmania (Viannia) braziliensis, em área de treinamento militar na Zona da Mata de Pernambuco

Abstract: RESUMO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 17 publications
1
6
0
4
Order By: Relevance
“…Similarly, a study conducted in a military training area in Paudalho reported a high diversity of phlebotomine sandflies, with the predominance of Lutzomyia complexa and Lutzomyia choti 3,5 .…”
Section: Occurrence and Distribution Of Vectorsmentioning
confidence: 83%
See 2 more Smart Citations
“…Similarly, a study conducted in a military training area in Paudalho reported a high diversity of phlebotomine sandflies, with the predominance of Lutzomyia complexa and Lutzomyia choti 3,5 .…”
Section: Occurrence and Distribution Of Vectorsmentioning
confidence: 83%
“…However, L. whitmani is predominant in most of the ACL transmission foci, mainly in domestic and peridomestic areas, whereas L. complexa or other species prevail in wild environments 5 . Compared with other northeastern Brazilian states, the phlebotomine sandfly fauna of Pernambuco is more diverse than Alagoas, Ceará, Paraíba, Piauí, Rio Grande do Norte, and Sergipe but not Maranhão and Bahia…”
Section: Occurrence and Distribution Of Vectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…O relato de casos da doença em militares após treinamento tem acontecido com frequência na Região Amazônica 9 . No CIMNC, após o primeiro surto investigado em 1996 4 , tem se verificado a ocorrência de um número importante de casos de LTA após os treinamentos militares 1 .…”
unclassified
“…Considerando-se a série histórica de casos de LTA na região, verifica-se que se trata de uma importante área de transmissão 1 . No entanto, ressalta-se que, após a intensificação das atividades de prevenção e controle por parte das organizações militares (OM), em seguida ao surto de 1996, houve importante controle da LTA na região.…”
unclassified